The mind and the hand. (March 2023) - Hobby, Jonathan; Ring, David; Larson, Debbie
Symptoms are determined in large part by mindsets. Feelings of distress and unhelpful thoughts (misinterpretations) of symptoms account for much of the variability in comfort and capability with the severity of the underlying pathophysiology making a more limited contribution. Incorporating this experimental evidence into the daily practice of hand surgery will help us find ways to develop healthy mindsets, to prioritize the alleviation of distress and the gentle redirection of unhelpful thoughts, to avoid unnecessary surgery, and to provide better psychological and social support for people recovering from injury and surgery.